Kemampuan Pck (Pedagogical Content Knowledge) Calon Guru Biologi FKIP UMS Dalam Menyusun Rpp Tahun Ajaran 2015/2016 - Kharisma, Firlita Nurul; , Dra. Hariyatmi, M. Si (2016)
Teacher is one of the critical success factors of the learning process and candidate teacher must train their ability for creating lesson plans with either one of them Pedagogical Content Knowledge (PCK). PCK is describe of merger between comprehension study (content knowledge) and pedagogy (pedagogical knowledge) that mixed grow into one at teacher. The purpose of this study is to know PCK ability of candidate teacher FKIP UMS in creating lesson plans. The study population was 136 students. Samples were taken by random sampling are students ever applying curriculum 2013 totaling 20 students, each three lesson plans. PCK date taken from the assessment of result lesson study in three categories are CK, PK, and PCK. The result showed that PCK scores of Biologi teachers candidate FKIP UMS year 2015/2016 are good category, results of CK value by percentage 60,83% (good), result of PK value by percentage 60,83% (good), and result of PCK value by percentage 71,58% (good). Totally result showed that PCK 71,6% (good). So that it can be said that PCK ability of biology teachers candidate FKIP UMS in creating lesson plans are good (71,6%).